The Complete Mitogenome of Elymus sibiricus and Insights Into Its Evolutionary Pattern Based on Simple Repeat Sequences of Seed Plant Mitogenomes - Xiong, Yanli; Yu, Qingqing; Xiong, Yi; Zhao, Junming; Lei, Xiong; Liu, Lin; Liu, Wei; Peng, Yan; Zhang, Jianbo; Li, Daxu; Bai, Shiqie; Ma, Xiao (Frontiers in Plant Science, 2022)
The most intriguing characteristics of plant mitochondrial genomes (mitogenomes) include their high variation in both sequence and structure, the extensive horizontal gene transfer (HGT), and the important role they play in hypoxic adaptation. However, the investigation of the mechanisms of hypoxic adaptation and HGT in plant mitochondria remains challenging due to the limited number of sequenced mitogenomes and non-coding nature of the transferred DNA. In this study, the mitogenome of Elymus sibiricus (Gramineae, Triticeae), a perennial grass species native to the Qinghai-Tibet plateau (QTP), was de novo assembled and compared with the mitogenomes of eight Gramineae species. The unique haplotype composition and higher TE content compared to three other Triticeae species may be attributed to the long-term high-altitude plateau adaptability of E. sibiricus. We aimed to discover the connection between mitogenome simple sequence repeats (SSRs) (mt-SSRs) and HGT. Therefore, we predicted and annotated the mt-SSRs of E. sibiricus along with the sequencing of 87 seed plants. The clustering result based on all of the predicted compound mitogenome SSRs (mt-c-SSRs) revealed an expected synteny within systematic taxa and also inter-taxa. The mt-c-SSRs were annotated to 11 genes, among which “(ATA)3agtcaagtcaag (AAT)3” occurred in the nad5 gene of 8 species. The above-mentioned results further confirmed the HGT of mitogenomes sequences even among distant species from the aspect of mt-c-SSRs. Two genes, nad4 and nad7, possessed a vast number of SSRs in their intron regions across the seed plant mitogenomes. Furthermore, five pairs of SSRs developed from the mitogenome of E. sibiricus could be considered as potential markers to distinguish between the species E. sibiricus and its related sympatric species E. nutans.